Effects of Company Size, Profitability, Solvability and Audit Opinion on Audit Delay - Syaiful Bahri; Rifa Amnia (Master of Accounting Universitas Trunojoyo Madura, 2020)
This study aims to analyze the effect of company size, profitability, solvency, and audit opinion on audit delay. The population of this study is LQ-45 companies listed on the Indonesia Stock Exchange in 2017-2018, but the samples employed in this study were 31 companies. The type of research data is a quantitative data of secondary sources, which analyzed with descriptive statistical analysis, classical assumption techniques, multiple linear regression analysis, coefficient of determination R² and t test. The results of this study of solvency variables affect audit delay with a significant value of 0,000. Firm size variable has no effect on audit delay with a significant value of 0.490. The profitability variable does not affect the audit delay with a significant value of 0.098. The audit opinion variable does not affect the audit delay with a significant value of 0.313.